KEABSAHAN STANDART KONTRAK YANG DIBUAT TERLEBIH DAHULU FORMATNYA DI TINJAU MENURUT PASAL 1320 KUH PERDATA JO PASAL 1338 KUH PERDATA - HENRY HIDAYAT AZZHAR (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTRegarding the validity of standard agreements that in this case the agreement between Perusda taps with the fact that the customer is considered to contain weakness especially if connected or in terms of Article 1320 Article 1338 BW BW Jo. Said to contain a weakness because the agreement contained no standard agreement (consensus) in the broad sense of the two sides, but only one-sided. While the applicant in giving the deal is only fictitious. Thus the standard agreement not only contains a weakness, but also deviated from the principles contained in Article 1320 BW 1338 BW Jo chapter. So it can be said of the legality standard agreement when viewed from Article 1320 Article 1338 BW BW Jo formally it can be said that the agreement is not valid standards. But this case we are faced with the problems that inevitably recognize the existence of a standard agreement as a means to meet the many needs of the community in supporting the survival, growth becomes vital as a means of fulfilling the primary requirement.Attachment problems of the parties to the standard agreement of the parties is able to foretell anything, as long as it is not contrary to law and morality, and what was agreed legally binding like a law. In relation to the standard agreements held by Perusda taps and customers or consumers, as long as it is agreed upon standard agreement and there is no injured party then the agreement is considered valid as stated in article 1338 paragraph (1) BW. Moreover, the standard agreement which became the object of the agreement is a vital means (water consumed) which is a primary need that is impossible to ignore by all humans in his life. This should be acknowledged its existence.